Analisis Kesulitan Belajar Matematika Siswa Kelas V SDN 007 Pangkalan Baru pada Operasi Hitung Perkalian dan Pembagian - Adhariani, Meisy; Siti Quratul Ain (PT PUSTAKA CENDEKIA GROUP, 2025)
This study aims to analyze the learning difficulties experienced by fifth-grade students of SDN 007 Pangkalan Baru in mathematics, specifically in multiplication and division operations. This research employed a qualitative approach with a descriptive phenomenological method. The research subjects consisted of the classroom teacher and fifth-grade students of SDN 007 Pangkalan Baru. Data were collected through tests, observations, and interviews, and were analyzed using Miles and Huberman’s interactive analysis model, which includes data reduction, data display, and conclusion drawing with verification. The results showed that students encountered learning difficulties in three main aspects: (1) difficulty in understanding concepts, (2) difficulty in understanding principles, and (3) difficulty in computational skills. The factors causing these difficulties were both internal and external. Internal factors included low learning motivation, lack of self-confidence, and weak memory of calculation procedures, while external factors included conventional teaching methods and insufficient family learning support. Based on the findings, it is suggested that teachers implement contextual learning strategies, utilize concrete media, and provide gradual practice to help students better understand the concepts of multiplication and division.